Macro-anatomical investigations on the forelimb skeleton of mole-rat (Spalax leucodon Nordmann) - Özkan, Zait Eender (My University, 2002)
In this study, five mole-rats (Spalax leucodon Nordmann) were used to investigate the bones of fore limb. It was observed that the area of fossa infraspinata (46%) was larger than that of fossa supraspinata (39%) Cylindrical, slender, curved clavicles about 1.52 cm long were observed. The humerus was peculiar and the ridges and the tuberosities were well developed. There was no supratrochlear foramen. The radius and ulna were distinct but in one mole-rat while the left radius and ulna were distinct and the right radius and ulna were fused. In the carpal proximal row, os carpi radiale and os carpi intermedium were fused (os carpi intermedioradiale). The manus was complete, with five digits. There were two phalanges in the first digit and the other four digits were composed of three phalanges. In the palmar face of the manus there were radial and ulnar sesamoids (ossa sesamoidea palmaria) with an irregular surface.
Keywords: Anatomy; Mole-rat; Ossa membri thoracici; Spalax leucodon